World happiness report 2013 - Helliwell, John F.; Layard, Richard; Sachs, Jeffrey (Sustainable Development Solutions Network, 2013)
The World Happiness Report reviews levels of happiness across developed and developing nations, and presents ranking tables on national and regional happiness. The first report in 2012 featured a broad examination of the data; this second report in 2013 considers more specific issues in measurement, explanation, and policy.